The macroeconomic environment of business core concepts and curious connections - Levi, Maurice D. 1945- (World Scientific, 2014)
This book provides an introduction to principal macroeconomic phenomena: inflation, unemployment, national income, interest rates and exchange rates. It describes how each phenomenon is measured, what makes it change and the consequences of change. The goal is to provide a degree of literacy about the economy which constitutes the environment of business.